b - e (Philadelphia, Fortress Press, 1969)
A selection of 143 Old and New Testament stories from the creation of earth to the conversion of Saul.
"The text on the Jerusalem translation has been altered for younger readers or listeners."--Jacket.
London ed. (Darton, Longman & Todd) has title: Bible stories for children.
Keywords: Bible stories, English; Bible stories